73=-6g+97

Simple and best practice solution for 73=-6g+97 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 73=-6g+97 equation:


Simplifying
73 = -6g + 97

Reorder the terms:
73 = 97 + -6g

Solving
73 = 97 + -6g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '6g' to each side of the equation.
73 + 6g = 97 + -6g + 6g

Combine like terms: -6g + 6g = 0
73 + 6g = 97 + 0
73 + 6g = 97

Add '-73' to each side of the equation.
73 + -73 + 6g = 97 + -73

Combine like terms: 73 + -73 = 0
0 + 6g = 97 + -73
6g = 97 + -73

Combine like terms: 97 + -73 = 24
6g = 24

Divide each side by '6'.
g = 4

Simplifying
g = 4

See similar equations:

| 33.6=H^3/2 | | 8p=97 | | j+23=3 | | 12=6a+2 | | 3x+7y+23=30 | | m=(h-w)/8 | | 7=6c+1 | | 3+4(t+2)=2t-2 | | -y+244=179 | | j+23=-s | | 11+4x+2+3x=90 | | P-3+8=8 | | 0.5(3z+7)+17.7=0.7(3z-4) | | -0.72m=-2 | | 73=9h+1 | | A+B=4X-2 | | 14-3p+1=4+p | | 3.33=-.5 | | 185=35-x | | 750+0.2=1050 | | A+B=4X-8 | | (5.3x+8.2y)+(13.3y-4.1x)= | | 0=8n+7n | | 5x-7.1111=64 | | 3x+7x-3.5=2 | | x-10+2x+30=180 | | 25x-10+58=180 | | 6(5x+5)+4x= | | y-4x=-14 | | 3/8*16= | | 2(d+1)=-38 | | 12n+7=7n+15 |

Equations solver categories